Association of Serum Ferritin Levels With Acute Coronary Syndrome: A Case Control Study - B. Shinde, Aditya; S. Kuthe, Shilpa; M. Bhagwatkar, Hitendra (Journal of Neonatal Surgery, 2025)
Background: Acute coronary syndrome (ACS) remains a leading cause of morbidity and mortality worldwide. Recent studies have highlighted the potential role of serum ferritin as a biomarker in cardiovascular diseases. This study investigates the association between serum ferritin levels and ACS and evaluates its potential as a prognostic marker. Methods: A case-control study was conducted at a tertiary healthcare center from July 2022 to October 2024, enrolling 50 ACS patients and 50 age- and sex-matched controls. Serum ferritin levels were measured using enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using logistic regression to assess the independent association of serum ferritin with ACS, adjusting for confounders such as diabetes mellitus, hypertension, and obesity. Results: Mean serum ferritin levels were significantly higher in ACS patients (315.18 ± 151.59 μg/L) compared to controls (117.88 ± 89.48 μg/L) (p < 0.001). Multivariate logistic regression demonstrated that high serum ferritin (>300 μg/L) was an independent predictor of ACS (OR = 68.4, 95% CI: 9.35 - 500.45, p = 0.001), even after adjusting for traditional risk factors. Conclusion: Elevated serum ferritin levels are significantly associated with ACS, suggesting its potential role as a biomarker for cardiovascular risk assessment. Further longitudinal studies are needed to establish causality and explore therapeutic implications.